E-LEARNING AS AN INSTRUMENT ENSURING NATIONAL COMPETITIVE ADVANTAGES DEVELOPMENT AND THE SOURCE OF NATIONAL SECURITY THREATS - Andrey S. Zuev (Высшее образование в России)
Electronic training and e-Learning technologies, including open educational resources and mass open online courses are considered as a source of national security threats and the instrument of national competitive advantages development. Consideration of aperspective of their implementation is carried out taking into account features of the main educational content consumers - so called “digital generations”. Their socialization took place and proceeds in the conditions of information society formation.